Evaluasi Wastage Level Material Struktur (Besi, Kayu, dan Beton) pada Proyek Rumah Susun Pemerintah di Surakarta - Heribertus Nurbawono Budiharsanto; Mardiaman Mardiaman (Jurnal Talenta Sipil, 2026)
The construction industry is one of the sectors with a high level of material waste, particularly in structural works of building projects. Material waste not only leads to project cost inefficiencies but also increases environmental burdens and contradicts the principles of sustainable construction, especially in government-funded apartment projects that demand high accountability. Therefore, evaluating material waste based on actual field data is essential to improve material management performance. This study aims to evaluate the level of material waste (wastage level) of structural materials, including reinforcing steel, formwork plywood, and concrete, in a government apartment project in the City of Surakarta. The research employed a descriptive quantitative approach with a case study method, using a comparison between material acceptance data and actual material usage during the execution of structural works. The results indicate that reinforcing steel exhibits the highest average wastage level at 13.38%, followed by plywood at 9.90%, while concrete shows the lowest wastage at 2.50%. The highest wastage in steel materials occurs in M6 wiremesh, reaching 55.74%, whereas the highest plywood wastage is found in 12 mm plywood at 17.73%. The relatively low concrete wastage reflects the effectiveness of ready-mix concrete procurement systems in controlling material volume and minimizing residual waste.Based on these findings, it is recommended to improve steel cutting planning, select more durable formwork materials, and strengthen on-site material control to reduce material waste and support the implementation of sustainable construction practices in government housing projects.